Serum miRNAs as predictive and preventive biomarker for pre-clinical hepatocellular carcinoma. Issue 2 (10th April 2016) - Li, Liang; Chen, Jianguo; Chen, Xin; Tang, Jing; Guo, Huan; Wang, Xiaofeng; Qian, Ji; Luo, Guijuan; He, Fangping; Lu, Xiaomei; Ding, Yibo; Yang, Yingchen; et al.
Highlights: A multicenter, retrospective and longitudinal phase 3 biomarker study is conducted. A five-miRNAs set is identified as pre-clinical screening biomarker for HCC. The five-miRNAs set has higher sensitivity than AFP to distinguish pre-clinical HCC. The five-miRNAs set identifies pre-clinical HCC regardless of AFP or cirrhosis status. The five-miRNAs set identifies pre-clinical HCC 6–12 months before clinical diagnosis. Abstract: The extremely poor prognosis of patients with symptomatic hepatocellular carcinoma (HCC) diagnosed clinically at advanced stages suggests an urgent need for biomarkers that can be used for prospective surveillance and pre-clinical screening for early presence of pre-malignant lesions and tumors. In a retrospective longitudinal phase 3 biomarker study in seven medical centers of China, time-series and 6 months interval-serum samples were collected from chronic hepatitis B virus infected (CHB) patient cohorts at the pre-malignant or pre-clinical stages (average 6 months prior to clinical diagnosis) and CHB patients that did not develop cancer, and circulating miRNAs measured. A set of serum miRNAs including miR-193a-3p, miR-369-5p, miR-672, miR-429 and let-7i* were identified in pre-clinical HCC patients and have the potential to screen for CHB patients at high risk to develop HCC 6–12 months after miRNAs measurement. These circulating miRNAs combined with the conventional screening tools using α-fetoprotein and ultrasound, may have great promise for the prediction and prevention of HCC in high-risk populations.